Pain Viewed from the Outside: A Response to Verpaelst - Perreault, Kadija (BioéthiqueOnline, 2015)
Pain is a subjective experience. Gaining insight from persons in pain into what it is to live with pain is important for clinicians, teachers and researchers. Being exposed to art created by persons in pain is one way to help understand these lived experiences.